2013
DOI: 10.1111/nan.12040
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of autophagic proteins in the skeletal muscle of sporadic inclusion body myositis

Abstract: The overexpression of autophagy markers linked to the decreased clearance of misfolded proteins, including SMI-31, and rimmed vacuoles accumulation may exhaust cellular resources and lead to cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 71 publications
2
24
1
Order By: Relevance
“…Impaired autophagosome maturation with consequent accumulation of multiprotein aggregates is considered a key factor in the myofiber degeneration and muscle weakness characteristic of sIBM [8][10]. However, it is unclear whether the autophagic pathway is also altered in other IIMs [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired autophagosome maturation with consequent accumulation of multiprotein aggregates is considered a key factor in the myofiber degeneration and muscle weakness characteristic of sIBM [8][10]. However, it is unclear whether the autophagic pathway is also altered in other IIMs [36].…”
Section: Discussionmentioning
confidence: 99%
“…Since autophagy has such a large range of physiological functions, it is unsurprising that its dysregulation contributes to several human diseases, including cardiac dysfunction, diabetes, neurodegenerative disorders (Huntington’s, Alzheimer’s and Parkinson’s diseases), cancer, and autoinflammatory/autoimmune diseases [7], including sporadic inclusion body myositis (sIBM) [8][10], in which it seems to be responsible for the accumulation of the multiple protein aggregates characteristic of the muscle fibers of this disease [8]. The mechanisms of autophagy dysregulation in sIBM are unknown, and clear descriptions of autophagic processes in other idiopathic inflammatory myopathies (IIMs), specifically polymyositis (PM), dermatomyositis (DM) and juvenile dermatomyositis (JDM) are also lacking.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, studies have shown the presence of betaamyloid and tau deposits, as well as accumulation of several other proteins known to be involved in other neurodegenerative diseases, such as TDP-43. Other studies have also shown accumulation of autophagy-related proteins, such as LC3 and p62 [21][22][23]. Although more research needs to be done, these proteins may prove useful both in diagnosing and understanding the pathology of IBM.…”
Section: Inclusion Body Myositismentioning
confidence: 94%
“…A more recent immunohistochemistry study reports overexpression of the autophagy proteins ATG5, microtubule‐associated protein light chain 3 (LC3) and Beclin‐1 in IBM muscle biopsies. Interestingly, lymphocytic infiltrates were predominantly found surrounding Beclin‐1 + myofibers 261. Recently, components of chaperone‐mediated autophagy were identified to be increased in IBM as well 262.…”
Section: Degenerative Pathomechanisms In Ibmmentioning
confidence: 99%